PENERAPAN MODEL PEMBELAJARAN EXPLICIT INTRUCTION UNTUK MENINGKATKAN KEMAMPUAN TARI PASAMBAHAN SISWA KELAS V SDN 161 PEKANBARU - Pratiwi, Cecilia Hana; Antosa, Zariul; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :  The background of this research is the low ability students in dance dancing Pasambahan on SDN 161 pekanbaru in learning the art of culture and skills of teachers due to lack of knowledge in mastering the learning material , not master of traditional dance movements of other regions and children do not know about other areas of traditional dance movements . This research was conducted with the aim to improve the ability Pasambahan dance with the application of Explicit Instruction Model .Based on data analysis activities of the average teacher meeting I 60 1 cycle with enough categories, the 2nd meeting of the first cycle to 70 in both categories. Cycle II meeting 1 the average activity of teachers increased to 80 categories of good, the 2nd meeting of the second cycle increased to 85 in both categories, rose again on the third cycle of 1-90 meeting with either category, rising at the 2nd meeting of the third cycle to 95 with a very good category. Average student activity meets the first cycle 1 at 50% categorized fairly, increasing at a meeting to-2 with 55% categorized enough. At the first meeting of the average student activity second cycle increased to 60% with enough categories, at a meeting to-2 increased to 70% in both categories. 1 satisfy the average student activity cycle III 90%, increase in III-2 meeting cycle to 95%. From the results of the activities of teachers and students showed improvement. Assessment results of basic dance movements to improve the average value creation at the beginning of the data is 40.9, the ability to improve assessment creation first cycle of basic dance movements with an average of 50.1 from the preliminary data. On assessment results improve basic motor skills creation dance second cycle average ability students increased to 71.2. In the third cycle of basic motor skills results penilaia dance creations by 83.1. Based on the above it can be concluded that the application of learning explicit instruction model can improve basic motor skills of dance creations students received at SDN 161 Pekanbaru.                                                                                                                                                            Key Words: Explicit Learning ModelIntruction, Creative Dance Basic Motion